Vasculitis with a neuromuscular presentation and associated cancer revealed by autopsy - Larry Nichols; Mathew Joseph Karivelil (University of São Paulo, 2021)
Peripheral neuropathy is common, but rarely due to vasculitis. This report is the case of a 74-year-old woman with systemic vasculitis who presented with progressive arm and leg weakness associated with numbness. Autopsy revealed a colon cancer, which may have triggered the vasculitis. This case illustrates the association between vasculitis and malignancy. The best treatment of vasculitis in patients with cancer-associated vasculitis is usually treatment of the cancer, which often yields remission of the vasculitis. This case also illustrates the difficulty of suspecting vasculitis since the symptoms and signs are nonspecific and protean. It is important not to miss a diagnosis of vasculitis. It is often life-threatening. It is treatable. The critical step in the diagnosis of vasculitis is to think of it.